Development of sensitization to peanut and storage proteins and relation to markers of airway and systemic inflammation: A 24‐year follow‐up. Issue 2 (14th November 2022) - Tedner, Sandra G.; Klevebro, Susanna; Bergström, Anna; Kull, Inger; Andersson, Niklas; Borres, Magnus P.; Ballardini, Natalia; Westman, Marit; Konradsen, Jon R.; van Hage, Marianne; Nilsson, Caroline; Melén, Erik; et al.
Abstract: Background: Long‐time data of peanut allergy over time is sparse. We aimed to study the longitudinal development of sensitization to peanut extract and storage protein allergen molecules and associations with asthma status, airway and systemic inflammation markers. Methods: The Swedish birth cohort BAMSE followed 4089 participants with questionnaires, clinical investigations and blood sampling between 0 and 24 years. Information on (i) background factors at 2 months, (ii) peanut allergy symptoms and IgE data (ImmunoCAP) at 4, 8, 16, and 24 years, and (iii) IgE to storage proteins, lung function data including exhaled nitric oxide (FENO) as well as systemic inflammatory markers at 24 years of age were collected. Results: The prevalence of peanut extract sensitization, defined as IgE ≥ 0.35 kUA /L, was 5.4%, 8.0%, 7.5%, and 6.2% at 4, 8, 16, and 24 years of age, respectively. Between 8 and 24 years of age, (33/1565) participants developed IgE‐ab to peanut extract (median 1, 4, range 0.7–2.6 kUA /L), and among those 85% were also sensitized to birch. Only six individuals developed sensitization to Ara h 2 (≥0.1 kUA /L) between 8 and 24 years of age, of whom three had an IgE‐ab level between 0.1–0.12 kUA /L. Storage protein sensitization was associated with elevated FENO, blood eosinophils and type 2 inflammation‐related systemic proteins. Conclusion: Sensitization to peanut extract after 4 years of age is mainly induced by birch cross‐sensitization and IgE to Ara h 2 rarely emerges after eight years of age. Storage protein sensitization is associated with respiratory and systemic inflammation. Abstract : The prevalence of peanut extract sensitization, defined as IgE≥0.35 kUA/L, is 5.4%, 8.0%, 7.5%, and 6.2% at 4, 8, 16, and 24 years of age, respectively. Most individuals with peanut sensitization at 24 years of age are sensitized to peanut extract already at 4 and 8 years. Individuals with sensitization to storage protein in peanut and/or tree nut at 24 years of age have higher levels of exhaled nitric oxide and blood eosinophils, both in asthmatics and non‐asthmatics, compared to individuals with other types of sensitization.Abbreviations: Ara h 2, Arachis hypogea 2, peanut allergen molecule; BAMSE, Barn/Children, Allergy, Milieu, Stockholm, Epidemiology; FeNo, exhaled nitric oxide; IgE, immunoglobulin E; kUA /L, kilounits of allergen specific sIgE‐ab per liter; MMP10, Matrix metalloproteinase‐10; NPX, normalized protein expression; TNFRSF11, tumor necrosis factor receptor superfamily 11